Tingkat Pemahaman Peserta Ekstrakurikuler Pecinta Alam Mayapada terhadap Keselamatan Pendakian Gunung di SMA Negeri 2 Ngawi - Negoro, Drajad Budi; Supriyono, Supriyono (Indonesian Journal for Physical Education and Sport, 2023)
This study aims to determine how high the level of understanding of Mayapada extracurricular students regarding mountain climbing safety at SMA Negeri 2 Ngawi. The type and design of this research is a survey with a design using quantitative descriptive research. In this study the population of all Mayapada extracurricular students at SMA Negeri 2 Ngawi, the sample was students from class X-XII and the sampling technique used simple random sampling method. The instrument used in this study was a questionnaire with a scale of 2 alternative answer. Testing the research instrument, namely testing the validity and reliability. Questionnaire data processing techniques using calculations assisted by SPSS media. The results of the research related to the level of understanding of Mayapada nature lovers extracurricular participants regarding the safety of mountaineering at SMA Negeri 2 Ngawi are in the “very low” category of 0% (0 students), the “low” category of 0% (0 students), the “very low” category moderate” by 3,3% (1 students), “high” category by 16,7% (5 students), “very high” category by 80% (24 students).